Direct Oral Anticoagulants Versus Traditional Anticoagulation in Cirrhotic Patients with Portal Vein Thrombosis: Updated Systematic Review - Xiulin Xiao M.S.; Wengen Zhu M.D.; Qixin Dai M.D. (Clinical and Applied Thrombosis/Hemostasis)
Background This systematic review aimed to evaluate the comparative effectiveness and safety of direct oral anticoagulants (DOACs) compared to traditional anticoagulation (vitamin K antagonists or low-molecular-weight heparins) in cirrhotic patients with portal vein thrombosis (PVT). Methods We conducted a literature search in PubMed and Embase databases up to May 2024. Studies were selected according to the PICOS criteria, focusing on cirrhotic patients with PVT treated with DOACs (dabigatran, rivaroxaban, apixaban, or edoxaban) compared to traditional anticoagulation. Results Our systematic review included four observational studies conducted in Japan, China, and the United States, involving a total of 223 patients with cirrhosis and PVT. The included studies collectively suggested that anticoagulation therapy, including DOACs, was associated with improved recanalization rates and reduced progression of PVT in patients with liver cirrhosis, without a significant increase in bleeding complications. Specifically, edoxaban demonstrated superior effectiveness in reducing PVT volume compared to traditional anticoagulation, while maintaining a favorable safety profile. Conclusion DOACs may provide a promising therapeutic option for PVT in cirrhotic patients. Further research is needed to confirm the potential benefits and risks of DOACs in this population.